Real exchange rates and primary commodity prices: Mussa meets Backus-Smith - Jo\~ao Ayres; Constantino Hevia; Juan Pablo Nicolini (Inter-American Development Bank (IDB), 2021)
We show that explicitly modeling primary commodities in an otherwise totally standard incomplete markets open economy model can go a long way in explaining the Mussa puzzle and the Backus-Smith puzzle, two of the main puzzles in the international economics literature.
Keywords: F31; F41; 330; Primary commodity prices; Mussa puzzle; Backus-Smith puzzle